The role of VvMYBA2r and VvMYBA2w alleles of the MYBA2 locus in the regulation of anthocyanin biosynthesis for molecular breeding of grape (Vitis spp.) skin coloration. Issue 6 (1st March 2021) - Jiu, Songtao; Guan, Le; Leng, Xiangpeng; Zhang, Kekun; Haider, Muhammad Salman; Yu, Xiang; Zhu, Xudong; Zheng, Ting; Ge, Mengqing; Wang, Chen; Jia, Haifeng; Shangguan, Lingfei; et al.
Summary: In grape, MYBA1 and MYBA2 at the colour locus are the major genetic determinants of grape skin colour, and the mutation of two functional genes ( VvMYBA1 and VvMYBA2 ) from these loci leads to white skin colour. This study aimed to elucidate the regulation of grape berry coloration by isolating and characterizing VvMYBA2w and VvMYBA2r alleles. The overexpression of VvMYBA2r up‐regulated the expression of anthocyanin biosynthetic genes and resulted in higher anthocyanin accumulation in transgenic tobacco than wild‐type (WT) plants, especially in flowers. However, the ectopic expression of VvMYBA2w inactivated the expression of anthocyanin biosynthetic genes and could not cause obvious phenotypic modulation in transgenic tobacco. Unlike in VvMYBA2r, CA dinucleotide deletion shortened the C‐terminal transactivation region and disrupted the transcriptional activation activity of VvMYBA2w. The results indicated that VvMYBA2r positively regulated anthocyanin biosynthesis by forming the VvMYBA2r‐VvMYCA1‐VvWDR1 complex, and VvWDR1 enhanced anthocyanin accumulation by interacting with the VvMYBA2r‐VvMYCA1 complex; however, R 44 L substitution abolished the interaction of VvMYBA2w with VvMYCA1. Meanwhile, both R 44 L substitution and CA dinucleotide deletion seriously affected the efficacy of VvMYBA2w to regulate anthocyanin biosynthesis, and the two non‐synonymous mutations were additive in their effects. Investigation of the colour density and MYB haplotypes of 213 grape germplasms revealed that dark‐skinned varieties tended to contain HapC‐N and HapE2, whereas red‐skinned varieties contained high frequencies of HapB and HapC‐Rs. Regarding ploidy, the higher the number of functional alleles present in a variety, the darker was the skin colour. In summary, this study provides insight into the roles of VvMYBA2r and VvMYBA2w alleles and lays the foundation for the molecular breeding of grape varieties with different skin colour.